الرحلات الاستطلاعية للأوربيين خلال العهد العثماني ودورها في التمهيد لاحتلال الجزائر(خلال القرنين 18-19م) - حواء حنكة (Universty Of El-oued جامعة الوادي, 2024)
الملخص: يعالج مضمون هذه الأطروحة: >الرحلات الاستطلاعية للأوروبيين خلال القرنين (18-19 م( ودورها في التمهيد لاحتلال الجزائر <، فبعد انضواء الجزائر تحت الراية العثمانية، وتميّزها بجيش بحري قوي بات يهدّد مصالح الدول الأوروبية، عرفت توافدا للعديد من الرحالة الأوروبيين بمختلف جنسياتهم وتخصّصاتهم لاستطلاع الأوضاع الساحلية والداخلية، بُغية القضاء على حركة الجهاد البحري التي أفشلت أغلب الحملات الموجّهة ضدّها، واستكشافًا للأوضاع الداخلية والمناطق المختلفة للبلاد تيسيرًا للسيطرة عليها، وقد قمنا بذكر الأوضاع العامة لأوروبا خلال القرنين16م و17م لنبيّن دوافع التوجه خارج القارة، وذكرنا الأوضاع العامة لإيالة الجزائر التي كانت سببًا في توافد الرحلات لاستكشاف أرضها، وتناولنا ماهية وأهداف الرحلات الاستطلاعية الأوروبية خلال القرنين 18م و19م هذه الأخيرة التي اختلفت عن الرحلات التي سبقتها، في موضوعها ومعلوماتها وأهدافها وممهّدات تغلغها داخل التركيبة السكانية الجزائرية ومناطقها الشاسعة، وخلصنا أخيرا أن فرنسا في تنفيذ غزوها اعتمدت على المؤلفات والمذكّرات والرسائل والتقارير التي دوّنها وأرسلها الرحالة، بل إن رحلاتهم الاستطلاعية باختلاف الدولة المرسلة كانت أرضية احتلال الجزائر، إن لم تكن موجّهة في الأساس إلى استكشافها قصد تعزيز فُرص الاستيلاء عليها. Abstract : Addresses the content of this Thesis: European Reconnaissance trips during the two centuries (18-19 M) and its role in preparing the ground for the occupation of Algeria, after Algeria's accession under the Ottoman banner, Distinguished by a strong naval army that threatens the interests of European States, I know of the presence of many European travellers of their various nationalities and specializations to explore coastal and internal situations. In order to eliminate the maritime jihad movement that has failed most of the campaigns against it and exploring the country's various internal and regional situations to facilitate their control, and we have mentioned the general conditions of Europe during the 16th and 17th centuries to show the motives of the trend outside the continent And we mentioned the general conditions of Algeria's referral, which caused the flight to explore its land, We addressed what were the objectives and objectives of the European reconnaissance flights during the 18th and 19th centuries, which differed from those that preceded them. s population and its vast regions, Finally, in carrying out its invasion, France relied on literature, notes, letters and reports written and sent by travellers. even their reconnaissance Trips by the sending State were the ground of Algeria's occupation, if they are not primarily aimed at being explored with a view to enhancing opportunities for seizure
أطروحة دكتوراه التخصص: الأدب العالمي و المقارن في العلوم الاجتماعية والانسانية
Keywords: الرحلات الاستطلاعية، الجزائر، العهد العثماني، الغزو الفرنسي، أرضية الاحتلال; Reconnaissance Trips; Algeria; Ottoman era; French invasion; Occupation ground